2021
DOI: 10.1029/2021gl096714
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Strokes Along the Same Channel to Ground in Positive Lightning Produced by a Supercell

Abstract: Previous studies have shown that subsequent leaders in positive cloud‐to‐ground lightning (+CG) flashes rarely traverse pre‐existing channels to ground. In this paper, we present evidence that this actually can be common, at least for some thunderstorms. Observations of +CG flashes in a supercell storm in Argentina by Córdoba Argentina Marx Meter Array (CAMMA) are presented, in which 54 (64%) of 84 multiple‐stroke +CG flashes had subsequent leaders following a pre‐existing channel to ground. These subsequent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 42 publications
6
15
0
Order By: Relevance
“…Similarly to Zhu et al. (2021), we observed that subsequent strokes occur after some negative leader branches stop propagating. Therefore, the presence of decayed negative channels seems to be a key aspect in multiple positive strokes.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Similarly to Zhu et al. (2021), we observed that subsequent strokes occur after some negative leader branches stop propagating. Therefore, the presence of decayed negative channels seems to be a key aspect in multiple positive strokes.…”
Section: Discussionsupporting
confidence: 87%
“…Our interferometer and LMA data do not show a slow positive recoil leader of several milliseconds before the subsequent return stroke as observed by Zhu et al. (2021), but this is not necessarily in contradiction with their observations. Our instrumentation operates at a higher frequency radio band, and it is more suited to detect breakdown and streamer activity near the head of propagating leaders instead of in‐cloud current pulses.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations